2015
DOI: 10.1371/journal.pone.0115624
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the Effect of Semantic Congruency on Episodic Memory: The Role of Integration and Relatedness

Abstract: A fundamental challenge in the study of learning and memory is to understand the role of existing knowledge in the encoding and retrieval of new episodic information. The importance of prior knowledge in memory is demonstrated in the congruency effect—the robust finding wherein participants display better memory for items that are compatible, rather than incompatible, with their pre-existing semantic knowledge. Despite its robustness, the mechanism underlying this effect is not well understood. In four studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 68 publications
(102 reference statements)
9
88
0
Order By: Relevance
“…The objective of our study was to better characterize the contribution of distinctiveness at encoding to previous contradicting findings attributing mnemonic advantage to novelty and familiarity (Axmacher et al, 2010;Badham & Maylor, 2015;Bein et al, 2015;Gronau & Shachar, 2015;Hirshman et al, 1989;Kishiyama & Yonelinas, 2003;Meeter, Murre, & Talamini, 2004;Michelon et al, 2003;Schulman, 1974;Stoppel et al, 2009;Tulving & Kroll, 1995;van Kesteren et al, 2012). Across two experiments and using two behavioral measures we found that an experimental list-based distinctiveness manipulation-varying experimental proportions-differentially affected items encoded in a conceptually novel (incongruent) or familiar (congruent) context: Distinctiveness was monotonically correlated with memory performance and reaction time (RT) for items encoded in a novel context, whereas memory and RT performance for familiar items was overall stable across all proportion conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The objective of our study was to better characterize the contribution of distinctiveness at encoding to previous contradicting findings attributing mnemonic advantage to novelty and familiarity (Axmacher et al, 2010;Badham & Maylor, 2015;Bein et al, 2015;Gronau & Shachar, 2015;Hirshman et al, 1989;Kishiyama & Yonelinas, 2003;Meeter, Murre, & Talamini, 2004;Michelon et al, 2003;Schulman, 1974;Stoppel et al, 2009;Tulving & Kroll, 1995;van Kesteren et al, 2012). Across two experiments and using two behavioral measures we found that an experimental list-based distinctiveness manipulation-varying experimental proportions-differentially affected items encoded in a conceptually novel (incongruent) or familiar (congruent) context: Distinctiveness was monotonically correlated with memory performance and reaction time (RT) for items encoded in a novel context, whereas memory and RT performance for familiar items was overall stable across all proportion conditions.…”
Section: Discussionmentioning
confidence: 99%
“…and to indicate their "yes/no" response by pressing one of two possible keyboard keys. This task was chosen for compatibility with previous SCE studies (Bein et al, 2015;Schulman, 1974). Notably, novel stimuli (e.g., "purple BANANA") required a different response than familiar stimuli, further stressing their distinctiveness.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations